Xylitol and erythritol inhibit real-time biofilm formation of Streptococcus mutans - Loimaranta V; Mazurel D; Deng DM; Soderling E (BMC, 2022)
Background: Regular consumption of xylitol decreases the number of cariogenic streptococci in dental plaque. In vitro biofilm models to study the mechanism of xylitol action have been set-up, but the obtained results are contradictory. Biofilm growth is a dynamic process with time-specific characteristics that may remain undetected in conventional end-point biofilm tests. In this study we used an impedance spectroscopy instrument, xCELLigence Real Time Cell Analyzer (RTCA), that allows label-free, non-invasive real-time monitoring of biofilm formation, to explore effects of xylitol on biofilm formation by Streptococcus mutans. Based on the obtained information of biofilm dynamics, we assessed the number of viable bacteria, the polysaccharide content, and the expression levels of selected genes involved in glucan-mediated biofilm formation in different biofilm stages. Xylitol inhibition was compared with that of erythritol; another polyol suggested to have a positive impact on oral health.
Results: Our results showed that real-time monitoring provided new information of polyol-induced changes in S. mutans biofilm formation dynamics. The inhibitory effect of polyols was more pronounced in the early stages of biofilm formation but affected also the measured total amount of formed biofilm. Effects seen in the real-time biofilm assay were only partially explained by changes in CFU values and polysaccharide amounts in the biofilms. Both xylitol and erythritol inhibited real-time biofilm formation by all the nine tested S. mutans strains. Sensitivity of the strains to inhibition varied: some were more sensitive to xylitol and some to erythritol. Xylitol also modified the expression levels of gbpB, gtfB, gtfC and gtfD genes that are important in polysaccharide-mediated adherence of S. mutans.
Conclusion: The erythritol- and xylitol- induced inhibition of biofilm formation was only partly explained by decrease in the number of viable S. mutans cells or the amount of polysaccharides in the biofilm matrix, suggesting that in addition to reduced proliferation also the matrix composition and thereby the surface attachment quality of biofilm matrix may be altered by the polyols.